LEGAL COMPOSITION OF AVIATION RISK (SYSTEM-APPLIED ANALYSIS) - Беззубов, Дмитро Олександрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Objective: to define legal models of the specific features of aviation risk as an integral part of economic activity. Propose effective mechanisms to reduce aviation risks. Suggest author models of aviation risk operation Methods: the study was conducted using classical methods of scientific knowledge. Using the method of analysis, the elements of aviation risk are revealed. Using the synthesis method, variants of aviation risk are considered. Results: according to the results of the study, the types of aviation risk are identified according to the fields of operation. Identified and disclosed components of aviation risk as an element of aviation activities.